The Role of Tax Consultants in Improving Taxpayer Compliance in Samarinda - Aprilia, Pany; Kesuma, Agus Iwan (INOVASI: Jurnal Ekonomi, Keuangan, dan Manajemen, 2025)
The purpose of this research is to determine the role of tax consultants in enhancing taxpayer compliance in fulfilling their tax obligations in the city of Samarinda. This research is based on field phenomena where an increase in the number of registered taxpayers and those reporting their Annual Tax Returns (SPT Tahunan) at the Pratama Tax Service Office in Samarinda has been observed. There is also an increase in the number of taxpayers using tax consultant services and an increase in the number of tax consultants practicing in the city of Samarinda. Data in this study were obtained from informants, the Samarinda Tax Consultant Association, and the Samarinda City Tax Service Office. The informants in this study were taxpayers who use tax consultant services and the tax consultants themselves, using qualitative research methods and data collection techniques through interviews. This study obtained results and conclusions, namely: The role of tax consultants is to provide advice and considerations to taxpayers, which is one of the factors triggering taxpayers' compliance intentions. However, the decision to be a compliant taxpayer or not is entirely up to the taxpayer themselves